A dating method with 39Ar - Loosli, H.H. (Earth and Planetary Science Letters, 1983)
The principles of a dating method based on the cosmic-ray-produced radioisotope 39Ar are given. Technical requirements such as background and standard gas samples and gas proportional counting systems are described. With samples extracted from Greenland ice it can be demonstrated that39Ar ages agree with ages obtained by other methods. First results on ocean water samples show that with this isotope valuable information on ocean mixing and circulation can be expected.39Ar results on groundwater samples disagree for some aquifers with conventional14C ages; possible explanations are discussed, especially underground production of 39Ar.